They Can’t Take that Away from Me: An Indemnification Solution to Unmerited VARA Claims - Marber, Sinclaire (The Columbia Journal of Law & the Arts, 2018)
Artist Cady Noland rose to prominence during the art market boom of the 1980s with mixed-media installations that employed found imagery to comment on the darker side of American social identity. Her work has garnered the highest price ever paid at auction for the work of a living female artist. Despite critical and commercial success, Noland has expressed deep concern over what she considers the improper handling and presentation of her art by collectors, auction houses, and museums. She has likened the auction process to “cutting up a writer’s words and throwing them up in the air,” further stating, “[i]f I had known that everything would be flipping at auction, I would have made works that were impervious.” Noland’s idiosyncratic behavior likely would have remained art world gossip had she not become embroiled in several highly publicized lawsuits. Noland stopped creating new works altogether in 2001 and refuses to facilitate any exhibitions devoted to her career. For nearly two decades, she has spent her time monitoring older works and recently appeared to have discovered a method that may halt continued resales. In 2012, Noland began renouncing authorship of works that she is known to have created but which have allegedly deteriorated to the point that she no longer approves of them as “her art,” resulting in multiple legal actions.5 Because an artist’s acknowledgement rather than her hand typically defines whether a work is considered “original,” Noland’s disavowals have the potential to render her art unsaleable, inflicting financial harm upon the collectors who currently own the pieces. Who should absorb this sudden loss in value? This Note argues that market participants should be indemnified against legally baseless revocations of attribution by living artists. Noland justifies her disavowals under the Visual Artists Rights Act of 1990 (“VARA”), the American answer to the French concept of droit moral or moral rights.8 Moral rights provide artists with control over the integrity and attribution of their art even after it has been sold. In a narrow set of circumstances, VARA permits a living artist to disavow her works if they have been modified so extensively as to be prejudicial to the artist’s reputation (excepting changes caused by aging or conservation). But there is a dearth of case law defining terms like modification, prejudice, and reputation. Even among Noland’s disavowals there is variation: she revoked authorship of the aluminum print Cowboys Milking because she perceived wear on its corners, and of the wooden building façade Log Cabin because conservators allegedly rebuilt the entire piece without permission. Noland is one of relatively few artists to bring lawsuits under VARA, and research for this Note has uncovered no cases of an owner or other stakeholder suing an artist for improperly invoking VARA. Even if a party were to sue Noland for abusing VARA and successfully obtain an injunction forcing her to legally affirm authorship of a work, this would likely not remedy the market damage caused by her public disavowal. No matter the conclusion of a court, collectors are unlikely to invest millions of dollars in art unsupported by its creator. Unfortunately, moral rights law in the United States has not yet addressed this situation. This Note proposes that the indemnification solutions contained in the droit moral provide a possible solution to the problems that result when an artist disavows her art without legal cause.